1977
DOI: 10.1093/infdis/135.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Possible Endotoxemia in Rabbits after Intravenous Injection of Staphylococcus aureus Enterotoxin B

Abstract: Staphylococcus aureus enterotoxin B (SEB) administered intravenously may exert its toxicity by damaging capillary endothelium in the large intestine and, thereby, permit absorption of endotoxin into the circulation. To investigate this possibility, we measured an index of the level of plasma endotoxin. This index was the ability of plasma to cause gelation of limulus amebocyte lysate (GLAL), before and after intravenous administration of SEB (800-1,000 microng/kg of body weight) to 13 rabbits. All samples take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In studies on rabbits, 47 we found that iv injection of SEB resulted in appearance of appreciable levels (up to 1 /ig/ml) of endotoxin in plasma, presumably absorbed from the gut; death was associated with endotoxemia, and survival was associated with lack of endotoxemia. In the present study we obtained contrasting results in that endotoxin never was detectable in any of the monkeys despite measurement at repeated time intervals during enterotoxemia.…”
Section: Endotoxinmentioning
confidence: 85%
“…In studies on rabbits, 47 we found that iv injection of SEB resulted in appearance of appreciable levels (up to 1 /ig/ml) of endotoxin in plasma, presumably absorbed from the gut; death was associated with endotoxemia, and survival was associated with lack of endotoxemia. In the present study we obtained contrasting results in that endotoxin never was detectable in any of the monkeys despite measurement at repeated time intervals during enterotoxemia.…”
Section: Endotoxinmentioning
confidence: 85%
“…The values represent the mean ϩ SD for duplicate samples from three experiments. Numerous investigations show that LPS potentiates the biologic effects of SEs and that septic shock may reflect a culmination of excessive proinflammatory cytokines resulting from the actions of both toxins (3,4,24,35,39,40,42). Although SE and LPS often lead to different sequelae, acute shock caused by abnormally high levels of TNF-␣ and other proinflammatory cytokines results in life-threatening situations (8,11,38).…”
Section: Fig 2 Levels Of Tnf-␣ (A) Ifn-␥ (B) Il-1␣ (C)mentioning
confidence: 99%
“…As evidenced in mice with the various staphylococcal superantigens, different rabbit strains also possess varying susceptibility toward TSST-1 as New Zealand whites are more susceptible vs. Dutch belted 113 . As witnessed in humans with toxic shock, rabbits given TSST-1 or SEB experience elevated levels of circulating LPS eliminated by polymyxin B 113 , 114 . From a biodefense perspective, intrabronchial instillation of SEB (SEC or TSST-1 too) into rabbits can be useful for testing potential therapies and vaccines 115 .…”
Section: In Vivo Effects: Animal Models and Morementioning
confidence: 99%